Tradução intersemiótica e indústria cultural : clássicos da literatura no formato de histórias em quadrinhos - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
This study focuses on the search for different perspectives and theoretical and methodological approaches that benefit the studies about Intersemiotic Translation on aspects of the proposed theme – Classical Literature in Comics format – whose symbiosis with the Cultural Industry phenomenon will enable a more understanding concerning of the intersections between these two areas of artistic expression. The primary purpose is to analyze the strategies used in the translation of the work A Cartomante, by Machado de Assis, to the Comics, considering the esthetic elements, cultural and linguistic-discursive this process, and based on reflections offered by theories underlying studies about Intersemiotic Translation and Cultural Industry. The main issues in this study are centered around understanding how the process occurs in which a code or language belonging to a system of signs is translated to another system, and what are internal and external aspects that can be analyzed in relation to transposition of a literary classic to the comics format. As well, from a bibliographic reference is intended to devise a different perspective to the study of Intersemiotic Translation, specifically with regard to the translation of literary works to the comic format, and relating it to the culture industry, scrutinize new theoretical and methodological approaches to the study of this specific area. The use of these two epistemological bases - Intersemiotic Translation and Cultural Industry - occurs by the fact that when employed in isolation allow not cover, or understand the concrete totality involving appropriations and intersections between different areas of artistic expression, because it is necessary understand not only "how" but also "why" these transpositions are carried and become popular. And this means avoiding an analytical reductionism both formal aspects and content as the social and ideological aspects.
Keywords: Histórias em quadrinhos; Indústria cultural; Literatura; Tradução intersemiótica; Comics; Cultural industry; LIterature; Intersemiotic translation; LETRAS::LITERATURAS CLASSICAS